BODY SCRUB FORMULATION AND PHYSICAL QUALITY TEST OF TELANG FLOWER (Clitoria ternatea L.) EXTRACT - Syah maulana, Akhmad Jiddan (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2023)
Body scrubs are cosmetic preparations used for skincare. One of the natural ingredients that can be used as raw material for body scrubs is butterfly pea flowers, butterfly pea flowers also contain chemical compounds, namely flavonoids. Alkaloids, tannins, saponins, the content of butterfly pea flower flavonoids contains natural antioxidants. The purpose of this study was to determine the formulation and physical quality test of butterfly pea flower extract body scrub preparations. This research method is an experiment in making body scrubs by collecting materials to be extracted using the maceration method with 70% ethanol solvent. Performing formulations with extract concentrations of 1% and 3% and evaluating the physical quality test of body scrub preparations. The results of this study were obtained in the phytochemical screening, namely extracts containing flavonoid.Keywords: Butterfly pea flower, Body scrub, Physical quality test